Ethnomusicology, Queerness, Masculinity Silence=Death - Amico, Stephen (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book explores the disciplinary and recent interdisciplinary sites, relations, and productions of ethnomusicology and queerness, arguing that both are founded upon a destructive masculinity-indissolubly linked to coloniality and epistemic hegemony-and marked by a monologic, ethnocentric silencing of embodied, same-sex desire. Ethnomusicology's fetishization of masculinizing fieldwork; queerness's functioning as Anglocentric master category; and both spheres' devaluation of sensuality and experience, concomitant with an adherence to provincial, Western conceptions of knowledge production, are seen as precluding the possibility of an equitable, dialogic pluriversality. Ultimately reimagining the fates of both in relation to negative emotions and intractable affect, and enlisting the sonic as theoretical-material intervention, the disciplines are envisioned as vanquished, replaced by explorations of sound, sex/uality, and experiential somaticity occurring in a protean, postdisciplinary space of material/epistemic equity. This uncompromising and long-overdue critique will be of interest to researchers and students from numerous disciplinary and theoretical backgrounds, including music, sound, gender, queer, and postcolonial/decolonial studies. Stephen Amico is Associate Professor of Musicology at the University of Bergen, Norway. He is the author of Roll Over, Tchaikovsky!: Russian Popular Music and Post-Soviet Homosexuality (2014).